Factors affecting seasonal and spatial patterns of water quality in Lithuanian rivers - Gudas, Mindaugas; Povilaitis, Arvydas (Journal of Environmental Engineering and Landscape Management, 2013)
In this study the main processes influencing water quality of the Lithuanian rivers have been identified. Factor analysis was tested on river hydrochemical data from 108 sites for the period of 1999–2004. It enabled the identification of main factors determining water quality each season. As a result, monitoring stations were grouped into clusters each representing the influence of relevant factor. The tested multivariate statistical procedures can be applied in practice when the reasons for water quality impairments are to be investigated. The findings reveal that Wastewater factor is prominent in small rivers downstream larger towns; Agro-geological factor – in Northern Lithuania’s rivers of heavy carbonated soils and intensive agriculture lands as well as in South eastern Lithuania’s rivers of more acidic soils; Hardly degradable organics factor – in Northern and Middle Lithuania’s rivers of heavy-textured and fertile agricultural soils. The photosynthesis-vegetation and Aeration factors are predominant in major rivers. First published online: 14 Dec 2012